2015
DOI: 10.1016/j.tetlet.2014.12.102
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen–deuterium exchange of aromatic amines and amides using deuterated trifluoroacetic acid

Abstract: The H-D exchange of aromatic amines and amides, including pharmaceutically relevant compounds such as acetaminophen and diclofenac, was investigated using CF3COOD as both the sole reaction solvent and source of deuterium label. The described method is amenable to efficient deuterium incorporation for a wide variety of substrates possessing both electron-donating and electron-withdrawing substituents. Best results were seen with less basic anilines and highly activated acetanilides, reflecting the likelihood of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…12 However, this method was ineffective for more electron-poor substrates such as acetophenone and its derivatives, and the use of a homogeneous palladium catalyst in conjunction with CF 3 COOD was considered to improve the extent of deuteration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 However, this method was ineffective for more electron-poor substrates such as acetophenone and its derivatives, and the use of a homogeneous palladium catalyst in conjunction with CF 3 COOD was considered to improve the extent of deuteration.…”
Section: Resultsmentioning
confidence: 99%
“…5c The palladium-catalyzed ortho -selective H-D exchange of acetanilides was envisaged proceeding in a similar fashion to ketones under identical conditions. Our previous work 12 identified acetanilides as substrates well-suited for electrophilic H-D exchange in CF 3 COOD, so care was taken to identify any improvement in ortho -selective deuterium incorporation by catalyst 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study that used a D 2 O/D 2 SO 4 system found that conditions will lead to either partial or complete racemization of phenylalanine H/D exchange, which is indicated by the exchange of α-protons [79]. Deuterated TFA (TFA-d) is appropriate for slow H/D exchange [80], but its application to aromatic amides and amines [81] is less effective for more electron-poor substrates such as acetophenone and its derivatives [82]. In Scheme 17, a comparison can be made between phenylalanine 120 and tyrosine 121 treated with TFA-d [82] and TfOD [74,83].…”
Section: Multifunctional Features Of Deuterated Tfoh (Tfod)mentioning
confidence: 99%
“…On the basis of the time dependence of H/D exchange using TfOD as monitored by mass spectroscopy, the favored sites for H/D exchange can be summarized as the o-position with respect to the hydroxyl group on tyrosine > the hydrogen atoms of phenylalanine > the m-position with respect to the hydroxyl group on tyrosine. but its application to aromatic amides and amines [81] is less effective for more electron-poor substrates such as acetophenone and its derivatives [82]. In Scheme 17, a comparison can be made between phenylalanine 120 and tyrosine 121 treated with TFA-d [82] and TfOD [74,83].…”
Section: Multifunctional Features Of Deuterated Tfoh (Tfod)mentioning
confidence: 99%